A especificidade comunicacional do jornalismo a partir de uma fenomenologia pura: princípios a uma metafísica do estar-em-comunicação - Pereira, Guilherme Lucian (2015)
This work intend to investigate until certain point is possible to observe a configuration specifically communicational in the journalism as activity. In other words, how the result of these exercise, as a pretension of a relate-about, can be, certainly, an inherently communicative event? Therefore, will be relevant to consider the concept of informative intentionality – viewed as primacy that from emerge of the journalistic activity – beyond of your usual dimensionality, i.e., as a mere “orderer” of living experienced environment, until point to formulate a singular apprehension that lead to semantic circulation. Considering then a ποχη (epoché) as a perspective of phenomenological search, all the theoretical attempts will lead to pursuit for an essence of the communicational phenomenon until we can able to see the configuration yours on the modern journalism.